Reconfigurable water antennas - Hua, Changzhou (2015)
This paper introduces two types of reconfigurable water antennas. One is a water-grating leaky-wave antenna and the other is a sea-water monopole antenna. The water-grating leaky-wave antenna consists of a parabolic reflecting surface-wave launcher and a periodic water-grating structure, which is designed for wide-angle beam-scanning. While the sea-water monopole antenna mainly comprises of a Teflon container and a sea-water stream supplied by a water pump, which is very suitable for maritime wireless communications.